Comparison of time to engraftment between autologous patients receiving washed versus non-washed cryopreserved peripheral blood stem cell products. Issue 12 (2nd December 2018) - Reich-Slotky, Ronit; Makhani, Sarah S.; Vasovic, Ljiljana V.; Pearse, Roger N.; Rossi, Adriana; Philips, Adrianne; Cushing, Melissa M.; Singh, Amrita D.; van Besien, Koen
Abstract: Washing cryopreserved peripheral blood stem cell (PBSC) products can decrease infusion-related adverse reactions but can also result in cell loss and reduced cell viability. To assess the risk and benefit of washing products, we compared the time to neutrophil and platelet engraftment between autologous patients that received washed products ( n = 201) and non-washed products ( n = 89). The effect of the other variables, including age, gender, diagnosis, transplant dose, method of stem cell mobilization, and growth factor support regimen post-transplant, was assessed. In multivariate analysis, direct thaw and infusion of non-washed products resulted in significantly faster neutrophil engraftment ( p = .003) and platelet engraftment ( p = .017) than washed products. The mean neutrophil and platelet engraftment times were 1.07 days faster and 2.27 days faster, respectively. In conclusion, direct thaw and infusion of cryopreserved PBSC without washing results in significantly shorter time to recovery of neutrophils and platelets after autologous transplantation.